(untitled) (Journal of Tourism and Himalayan Adventures, 2022)
This paper is study about the intersection between yak herding and tourism. The main focus is on how the concepts of yak festival and gothstay are transforming the conventional notion of animal husbandry, in particular yak herding, in the eastern high mountain region of Nepal. It is based on ethnographic study among the yak and urang herders in the region. Triangulation methods i.e., observation, interview, household survey and GIS were used. The yak festival and the concept of gothstay are giving new meaning, value and symbol – something different from the customary usage – to yak and yak herding. The concept of yak-tourism is not only a connection of yak and yak herding with tourism, but also gendering of the yak through language, image and form in public spaces. Thus, the rational, instrumental and conventional way of describing of yak is not sufficient in the context of livestock tourism. Moreover, the concept of gothstay is transforming the traditional notion of goth; i.e., from herders’ place to touristic site for learning about Himalayan pastoral culture and lifestyle. It would be a potential alternative of livelihood source for the Himalayan herders who have very limited options for making a living.